Enhancing essential skills in basic education for sustainable future: Case analysis with exemplars related to local wisdom - Khar Thoe Ng; Phaik Lah Kim; Yoon Fah Lay; Yee Jiea Pang; Eng Tek Ong; Subuh Anggoro (Research Meets Innovation, 2021)
Supporting a quality basic education incorporating the 21st century curriculum to reach out to all including the marginalized groups has been a key priority globally including SEAMEO regions, especially for the past few decades. However, in the advent of the digital era with plentiful resources accessible from a multitude of blended-mode platforms, there are countries with limited resources such as accessibility to Internet connection still facing the problems to access to quality education. Attempts were made to meet the aspirations of Education for All (EFA) and Sustainable Development Goals (SDGs) over the past few decades through basic education reform. This article aims at analyzing the historical revolution of implementation of basic education for the past 2 decades, examine effective strategies that bridge the digital divide and showcase exemplary practices involving countries with potential local wisdom. Mixed-method design matrix is used involving systematic review, analysis on governmental official documents as well as case analysis through ‘Dominant model in qualitative research’. The implementation of basic education as a system-wide approach as well as effective strategies to enhance essential skills in basic education in line with SDGs was analysed using Cross-Case Analysis chronologically over the past more than two decades. Subsequently, Within-Case Analysis was conducted to showcase exemplary practices to integrate local wisdom in the respective educational systems in Cambodia, Malaysia, and Indonesia. This study was able to illustrate the practical significance of all co-authors who are the practitioners organizing the events as reported with research findings as analysed that are worth pondering for them to continue the efforts to organize project-based programmes with the development of basic education based on local wisdom. Most of the output was in line with all the Sustainable Development Goals (SDGs) especially No. 4 (Quality Education), No. 5 (Gender Equality), No. 11 (Sustainable Cities and Communities) and No. 17 (Partnerships for the Goals). Due to the various programmes that were elaborated in this paper being initiated at different points of time as the main constraints faced in terms of time and resources available, only selected cases were reported. Moreover, some of the activities were conducted during 2020 when all the countries were facing the constraints of being unable to conduct on-site events due to pandemic. But the lesson learnt that even robotics competition could also be conducted online raised one question to be pondered, ‘should basic education be implemented also based on local wisdom in collaboration with industrial partners to promote work or study from home’? More future research should be conducted to ensure that students acquire values and skills with meaningful lifelong learning to ensure inclusive and quality education is also the focus of SDG4-Education 2030 that emphasizes on lifelong learning approaches.